Bioinspired Passive Tactile Sensors Enabled by Reversible Polarization of Conjugated Polymers - He, Feng; Chen, Sitong; Zhou, Ruili; Diao, Hanyu; Han, Yangyang; Wu, Xiaodong (Nano-Micro Letters, 2024)
Tactile perception plays a vital role for the human body and is also highly desired for smart prosthesis and advanced robots. Compared to active sensing devices, passive piezoelectric and triboelectric tactile sensors consume less power, but lack the capability to resolve static stimuli. Here, we address this issue by utilizing the unique polarization chemistry of conjugated polymers for the first time and propose a new type of bioinspired, passive, and bio-friendly tactile sensors for resolving both static and dynamic stimuli. Specifically, to emulate the polarization process of natural sensory cells, conjugated polymers (including poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate), polyaniline, or polypyrrole) are controllably polarized into two opposite states to create artificial potential differences. The controllable and reversible polarization process of the conjugated polymers is fully in situ characterized. Then, a micro-structured ionic electrolyte is employed to imitate the natural ion channels and to encode external touch stimulations into the variation in potential difference outputs. Compared with the currently existing tactile sensing devices, the developed tactile sensors feature distinct characteristics including fully organic composition, high sensitivity (up to 773 mV N−1), ultralow power consumption (nW), as well as superior bio-friendliness. As demonstrations, both single point tactile perception (surface texture perception and material property perception) and two-dimensional tactile recognitions (shape or profile perception) with high accuracy are successfully realized using self-defined machine learning algorithms. This tactile sensing concept innovation based on the polarization chemistry of conjugated polymers opens up a new path to create robotic tactile sensors and prosthetic electronic skins. Highlights: 1 Fully organic and passive tactile sensors are developed via mimicking the sensing behavior of natural sensory cells. 2 Controllable polarizability of conjugated polymers is adopted for the first time to construct passive tactile sensors. 3 Machine learning-assisted surface texture detection, material property recognition, as well as shape/profile perception are realized with the tactile sensors.